Siri’ Killing vis-à-vis Honor Killing: Menimbang Batas Universal dan Kekhasan Lokal Pembunuhan Demi Kehormatan - Zul Khaidir Kadir (JOURNAL SAINS STUDENT RESEARCH, 2026)
The term honor killing has long been used in global scholarship to describe killings associated with the restoration of family or community honor. Although useful as a general category, the term does not always capture the full social meaning embedded in local experiences. This article examines the relationship between siri’ killing and honor killing by addressing two central questions: whether siri’ killing may be situated as a local form of honor killing, and to what extent it possesses conceptual features that are not fully covered by that global term. This study is a normative legal research employing conceptual and comparative approaches. The materials consist of primary legal sources, secondary legal materials, and relevant non-legal sources, all of which are analyzed qualitatively through library research. The study finds that siri’ killing may still be placed within the broader family of honor killing because both are grounded in the idea of family honor, the social spread of shame, and retaliatory violence understood as restoring dignity. At the same time, siri’ killing cannot be fully explained by the term honor killing because siri’ carries a more specific normative structure, particularly in relation to dignity, the distribution of shame, and the social responsibility to restore family reputation. This article argues that siri’ killing should be positioned as a local form that remains connected to honor killing while also correcting the overbreadth of that global concept. This distinction affects both criminological explanations of violence and criminal law’s effort to maintain a clear boundary between explaining social background and rejecting any justification for killing in the name of honor.